Law out of History, History by Law (KULT_online, 2018)
The multi- and interdisciplinary volume Law and Memory. Towards Legal Governance of History provides a variety of case studies in both national and international contexts to display the complexity and specificity of disputed laws dealing with historic memory. Tracing back legislations addressing different concerns about history and memory, from the Treaty of Westphalia to the current-day laws of the European Union, this volume contributes to debates on the ways in which law might interfere with or contribute to history writing and the construction of memory. Important questions on potentially prescribed practices of memorialization as well as the (in)compatibility of legal involvement in the shaping of knowledge of ‚historical truth‘ are raised. Furthermore, it brings into conversation not only different viewpoints from History and International Law to Ethics, but also controversial issues on nationalism and the (dis)advantages of transnational legislations. While the volume successfully accomplishes its intent to fill a gap in the current research on memory laws, the analysis of practices of remembrance in the collected texts could have benefitted from integrating methods and theories from established concepts of the study of memory.